Implementation and outcomes of standardized management on diabetes patients in eight provincial-level administrative divisions, China: a cross-sectional survey in 2018 - Sijia ZHANG; Xiaolei ZHU; Shiqi HU; Ye GENG; Xiaochang ZHANG; Jing WU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the implementation of diabetes health management project and its influence on knowledge awareness, health behavior, medication, and blood glucose control among the diabetes patients with the standardized management for the improvement of the project. MethodsUsing multistage random sampling, we recruited 3 995 diabetes patients aged 35 years and over and being followed-up in the Survey for Assessment on Chronic Disease Patients Management in the National Primary Public Health Services in 8 provincial level administrative divisions. A questionnaire survey and peripheral blood glucose test were conducted among the participants during August - October 2018. Binary logistic regression model was used to analyze the impact of standardized management on diabetes patients' knowledge awareness, health behavior, medication and blood glucose control. ResultsOf the 3 938 participants with complete information, 71.28%, 88.69%, 51.98% reported having standardized management (receiving 4 times and more health care follow-ups per year), medication for diabetes, and effective blood glucose control (fasting and postprandial blood glucose < 7.0 and < 10.0 mmol/L), respectively. Compared with those without standardized management, the participants with the management reported significantly higher ratios of relevant knowledge awareness (56.11% vs. 41.54%), better dietary diversity score (48.79% vs.43.26%), and effective blood glucose control (53.16% vs. 47.96%) (all P < 0.05) but significantly lower ratios of current smoking (10.17% vs. 12.49%) and alcohol consumption during past one year (13.34% vs. 18.78%) (both P < 0.05 ). Binary logistic regression analysis showed that the standardized management on diabetes patients was significantly correlated positively with the patients' better knowledge awareness and better dietary diversity, and negatively with the patients' current smoking and alcohol drinking (all P < 0.05). ConclusionThe standardized management on diabetes patients was positively related to the patients' better knowledge awareness and dietary diversity but negatively related to the patients' current smoking and alcohol drinking, suggesting that the management achieved good primary outcomes in China.